The transition school-university - Falcó de Jouas, Rosa; Aiello, María (2000)
This paper presents partial results of a research in the area of Vocational Occupational Guidance at the National University of San Luis on the subject "Transition School-University". The information offered here follows a survey on the relationship between the educational area and the organizations, persons and programs of the work and employment area. Reference is made to the information the different participants get as well as the importance they assign to said relationship. The interest of the results obtained is discussed with a view to optimize interventions in the speciality by taking into account the need of articulation of actions between the areas involved.
Keywords: Orientación vocacional; Trabajo; Empleo; Trabajo de investigación; Psicología ocupacional